A területi hatékonyság és jövedelemtermelő képesség változásának számítása az iparban - Bartke, István (Tér és Társadalom, 1987)
The general methodological principle adopted by the author is the scheme recommended by the Hungarian Central Statistical Office which relates production output to input according to their content and structure. This methodology was operationalized by quantifying the relationship between a net production indicator (the national income realized by industry) and an indicator for the normative revenue, the one 'to be expected' with regard to expenditures ('corrected national income'). Production dynamics are expressed by volume indices of a list of products. Expenditures and the 'normative revenue' which is made proportionate to expenditures are defined in a two-channel scheme starting from wages on the one hand and from the gross value of fixed assets on the other, with indicators using the former as a denominator. Both gross and net indicators can be used for calculating efficiency but the source of error is smaller if the calculation is based on net indicators than if it is done with gross data. The author calculated efficiency with both gross and net indicators partly to control and confirm the results; and the major interdependencies revealed indicated essentially similar tendencies. Both the gross and the net dynamic indicators used express, first of all, quantitative relationships; the qualitative aspects – in this case the changes in the marketability of products – were disregarded. The analysis demonstrated a further reinforcement of the spatial differentiation in efficiency that existed already at the beginning of the period investigated. During the almost two decades of the study period, the original high industrial efficiency in North-Transdanubia and in a large part of the Alföld (the Great Hungarian Plain) have further improved while the relatively poor position of the regions with important extractive industríes: North-Hungary, Komárom and Baranya counties) have further deteriorated. Divergence between the gross and the net indicators was only found in the case of Budapest in so far as the gross indicator showed a degradation while the net one indicated an improvement of efficiency. Changes in efficiency expressed by changes in the quantitative relationships between revenue and expenditures indicate the success of efforts made in order to save labour.